2009
DOI: 10.1093/ejo/cjp023
|View full text |Cite
|
Sign up to set email alerts
|

Enamel colour changes at debonding and after finishing procedures using five different adhesives

Abstract: The purpose of this study was to evaluate enamel colour alteration of five different orthodontic bonding adhesives by means of digital measurements after exposure to photoageing in order to simulate discolouration of adhesives in vivo. Seventy-five non-carious premolars were randomly divided into five equal groups. The brackets were bonded with five different adhesives (Transbond XT, Eagle Bond, Light Bond, Blugloo, Unite) and subjected to artificial accelerated photoageing for 24 hours. The enamel surfaces we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
73
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(81 citation statements)
references
References 18 publications
4
73
0
4
Order By: Relevance
“…However, comparatively few studies have investigated the effects of bonding materials used in brackets on enamel color (3,5,(8)(9)(10) and only 2 clinical studies examined the color alterations of teeth associated with FOT (3,4). According to the findings of those studies, visible enamel color changes may occur with fixed appliances, which would be detected in clinical trials (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…However, comparatively few studies have investigated the effects of bonding materials used in brackets on enamel color (3,5,(8)(9)(10) and only 2 clinical studies examined the color alterations of teeth associated with FOT (3,4). According to the findings of those studies, visible enamel color changes may occur with fixed appliances, which would be detected in clinical trials (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…Bonding materials have direct effect on tooth discoloration and ΔE between 0.85 to 1.51 units (Trakyali et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Several factors affect the natural color of the teeth, for example: the condition of the light coming from the surrounding environment, the color of gingival tissue and nature of the saliva that provides the tooth hydration, and the reflective index coming from the underlying surface (Goodkind & Schwabacher, 1987;Dawes, 1974). However, recent studies showed that bonding and debonding of brackets in orthodontic treatment may cause tooth discoloration (Eliades et al, 2001; Trakyali et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Otros autores han estudiado los cambios de color in-vitro del esmalte dental tratado con aditamentos fijos, por efecto del tipo de adhesivo utilizado [17][18][19][20]. En estos estudios, se analizó el efecto del envejecimiento de las resinas de un solo paso, el ionómero de vidrio y la resina fluida en el color del esmalte después de un tratamiento ortodóntico, encontrando una diferencia en el color por encima de 3,7 unidades ΔE, valor lími-te de diferencia propuesto como detectable por inspección visual, clínicamente [21].…”
Section: Introductionunclassified
“…El método más objetivo para determinar clínica-mente el color del esmalte dental es la espectrofotometría [16][17][18][19][20][22][23][24][25] utilizada tanto en estudios in-vitro como in-vivo. Este método permite el uso del sistema CIE (Commission Internationale de l'Eclairage) y los parámetros L, C y h [26].…”
Section: Introductionunclassified